A Synthesis of security valuation theory and the role of dividends, cash flows, and earnings* - OHLSON, JAMES A. (Contemporary Accounting Research, 1990)
Abstract. The paper reviews and synthesizes modern finance valuation theory and the ways it relates to the valuation of firms and accounting data. These models permit uncertainty and multiple dates, and the concept of intertemporal consistency in equilibria becomes critical. The key conclusions are (1) the basic theoretical insight derives from a powerful condition of no arbitrage; there is no role for complete markets in basic valuation theory; (2) only anticipated dividends can serve as a generically valid capitalization (present value) attribute of a security; (3) the notion of risk is general, and models such as the CAPM occur only as special cases; (4) the notion that one can capitalize cash flows rather than dividends requires additional (relatively stringent) assumptions; (5) existing theory of “pure” earnings under uncertainty lacks unity regarding their meaning and characteristics. It is argued that only one concept of “pure” earnings makes economic sense. In this case earnings are sufficient to determine a security's pay‐off, price plus dividends, consistent with some prior research but inconsistent with others. Résumé. L'auteur procède à l'examen et à la synthèse de la théorie moderne de l'évaluation financière et de la façon dont elle se rapporte à l'évaluation des entreprises et des données comptables. Les modèles utilisés prévoient les cas d'incertitude et de dates multiples, et la notion d'uniformité intertemporelle en situation d'équilibre revêt une importance critique. Les principales conclusions de l'auteur sont les suivantes: 1) le principe théorique fondamental dérive d'une forte situation de non‐arbitrage; 2) seuls les dividendes anticipés peuvent servir d'attribut de capitalisation (valeur actualisée) valide d'un titre sur le plan générique; 3) la notion de risque est générale, et les modèles tels que le modèle d'équilibre des marchés financiers ne se vérifient que dans des cas particuliers; 4) la notion de capitalisation des flux monétaires plutôt que des dividendes nécessite des hypothèses supplémentaires (relativement rigoureuses); 5) la théorie existante des bénéfices « purs » en situation d'incertitude manque d'unité en ce qui a trait au sens et aux caractéristiques de ces bénéfices. L'auteur affirme que la revue qu'il a effectvée de travaux antérieurs l'amène à conclure qu'un seul concept de bénéfices « purs » se justifie sur le plan économique pour déterminer le produit d'un titre qui comprenne à la fois le prix et les dividendes.